2018
DOI: 10.1097/j.pain.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-methods development of a new patient-reported outcome instrument for chronic low back pain: part 2—The Patient Assessment for Low Back Pain–Impacts (PAL-I)

Abstract: The Patient Assessment for Low Back Pain–Impacts is a newly developed patient-reported outcome instrument to assess specific impacts of chronic low back pain for use in clinical trials and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, the reported health transition (HT) is included. (4) Overall improvement as measured by the short-form McGill pain questionnaire (SF-MPQ) or symptom scale based on the Clinical Study Guideline for New Developed Chinese Medicine ( 29 31 ). The questionnaire can be used to assess the pain performance of patients with lower back pain, including the Pain Rating Index (PRI) calculated from the SF-MPQ scale where the PRI is the sum of sensory item scores and emotional item scores; the Visual Analog Scale (VAS) ( 27 , 32 ); and the Present pain intensity (PPI).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the reported health transition (HT) is included. (4) Overall improvement as measured by the short-form McGill pain questionnaire (SF-MPQ) or symptom scale based on the Clinical Study Guideline for New Developed Chinese Medicine ( 29 31 ). The questionnaire can be used to assess the pain performance of patients with lower back pain, including the Pain Rating Index (PRI) calculated from the SF-MPQ scale where the PRI is the sum of sensory item scores and emotional item scores; the Visual Analog Scale (VAS) ( 27 , 32 ); and the Present pain intensity (PPI).…”
Section: Methodsmentioning
confidence: 99%
“…The mean score for all assessed items (excluding withdrawal items) is a single overall assessment of the effect of pain on quality of life. PAL-I has demonstrated validity and potential utility for evaluating the efficacy of treating chronic BP in clinical trials [70]. In a multicenter observational study by Bushnell et al (2020) he also showed very robust estimates with substantial evidence of validity [71].…”
Section: Patient Assessment For Low Back Pain-impacts (Pal-i)mentioning
confidence: 99%
“…Its versatility, along with high specificity, gives PAL-I an advantage in research in a variety of chronic BP populations. In addition, PAL-I is currently the only tool for the subjective assessment of the effectiveness of drug therapy by a patient that fully complies with the recommendations of the US Food and Drug Administration (FDA) [70].…”
Section: Patient Assessment For Low Back Pain-impacts (Pal-i)mentioning
confidence: 99%
“…It also causes a huge economic loss ranging from 12.2 billion to 90.6 billion ( 6 ). In addition to pain and impaired function, CLBP limits leisure activities, social activities, and public engagements as well ( 10 ). Pain could negatively impact social relationships, such as poor relationships between children and peers ( 11 ) and reduced marital satisfaction between partners ( 12 ).…”
Section: Introductionmentioning
confidence: 99%